Low Self-Control, Peer Risk Factors, and Adolescent Vaping Activity - Boccio, Cashen (Crime & delinquency, 2024)
Recent research has identified several risk factors for adolescent vaping. However, limited research has directly explored how low self-control and peer vaping activity are related to adolescent vaping. This study addresses these gaps in the literature by examining relationships between low self-control, peer risk factors for vaping, and adolescent nicotine vaping using a sample of Florida adolescents collected in 2019. In addition, this study examines whether peer risk factors moderate the relationship between low self-control and nicotine vaping. The findings suggest that low self-control and peer nicotine vaping are linked with adolescent nicotine vaping. The findings also provide evidence that peer risk factors may moderate the relationship between low self-control and adolescent nicotine vaping.